Vaccine Strategy in Melanoma - Kwak, Minyoung (Surg Oncol Clin N Am, 2019)
The incidence of melanoma continues to increase even as advances in immunotherapy have led to survival benefits in advanced stages. Vaccines are capable of inducing strong, anti-tumor immune responses with limited toxicity. Some vaccines have demonstrated clinical benefit in clinical trials alone; however, others have not despite inducing strong immune responses. Recent advancements have improved vaccine design, while combining vaccines with other immunotherapies offers promise. This review highlights the underlying principles of vaccine development, common components of vaccines, the remaining challenges and future directions of vaccine therapy in melanoma.